City images: Cartagena de Indias and La Habana, in Love in times of cholera and The novel of my life (2008)
Based on proposals by Edward Soja and Benedict Anderson, this work offers a comparative reading between the way in which Cartagena city and La Habana city are represented in two contemporary novels. Love in  times of cholera and The novel of my life. The